Energy absorption behavior of oil palm empty fruit bunch fiber-reinforced composites subjected to low-velocity impact - Abdul Rahman, Mohd Khairul Faizi; Abdul Majid, Mohd Shukry; Abu Bakar, Shahriman; Md Tamrin, Shamsul Bahri; Israr Ahmad, Haris Ahmad; Ng, Yee Guan; Mohamad Razlan, Zuradzman (Sage Publications, 2023)
In this study, oil palm empty fruit bunch (OPEFB)-reinforced composites were subjected to a low-velocity impact test to study their energy absorption characteristics. Two sets of OPEFB-reinforced composite specimens were used, comprising 30:70 and 40:60 fiber/epoxy fractions. One set of specimens was treated with a 3 NaOH solution. The drop impact responses, fragmentation characteristics, energy absorptions, and residual strengths of both sets of specimens were analyzed. Drop impact tests were performed using three different energy levels, namely, 10, 13, and 16 J. In general, the results indicated that all the untreated specimens absorbed higher energy than that of the treated specimens, thus suffering severe surface and structural damage. This result is attributed to the treated specimens providing a better interlocking mechanism between the matrix and fibers and dissipating the impact energy through the impactor. Regarding fiber loading, all the 30:70 fiber/epoxy composites exhibited slightly less energy absorption than the 40:60 fiber/epoxy composites.